CO2 emissions in Indonesia: Key contributing factors and determinants - Aminy, Ika UA.; Inayah, Rahmatun; Saputra, Kormil; Jayatri, Adella U.; Hidayati, Dian M. (Narra Sains Indonesia, 2025)
Climate change is driven by increasing greenhouse gas emissions, particularly carbon dioxide (CO2). Developing countries such as Indonesia face a dilemma between meeting energy demands for development and reducing CO2 emissions. The aim of this study was to analyze trends of CO2 emissions in Indonesia during the period 1970–2023, utilizing secondary data from Our World in Data to obtain a comprehensive overview of national emission dynamics and Indonesia’s contribution at regional and global levels. A quantitative descriptive analysis method was applied using time-series data for the period 1970–2023, complemented by comparative analysis to evaluate temporal trends, dominant emission sources, and Indonesia’s proportional contribution at the Southeast Asia and global scales. The results indicate that Indonesia contributes approximately 3% of total global CO2 emissions and has the highest emission level in Southeast Asia, highlighting its strategic role in global climate change mitigation efforts. Historically, CO2 emissions in Indonesia showed a significant increase over the study period, rising from 3.37×108 tons in 1980 to 1.18×109 tons in 1984, largely due to economic growth from industrialization and increased energy consumption. The highest increase in CO2 occurred in 1997 due to forest fires and the El Niño phenomenon. Furthermore, the findings show that fossil fuel consumption, particularly coal, was the dominant contributor to national emissions in 2020. In conclusion, continued dependence on fossil energy remains a major challenge for Indonesia in achieving mitigation targets, underscoring the importance of energy transition and improved land-management strategies to curb future emission growth.